Evaluation of photodynamic therapy on fibroblast viability and cytokine production - Gomes Filho, João Eduardo [UNESP]; Araújo, Gustavo Sivieri de [UNESP]; Sipert, Carla Renata; Silva Santos, Ludmilla Mota da [UNESP]; Azevedo Queiroz, India Olinta de [UNESP]; Martins, Christine Men [UNESP]; Carmo Maia, Nayara Kivilla do [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Dezan Junior, Eloi [UNESP]; Bagnato, Vanderlei Salvador; Chaves Neto, Antonio Hernandes [UNESP]; Oliveira, Sandra Helena Penha de [UNESP] (Elsevier B.V., 2016)
Background: The aim of this study was to evaluate the effects of photodynamic therapy with curcumin (PDT) comparatively to 5% sodium hypochlorite (NaOCl) and saline solution on cell viability and cytokine (IL-1 beta and IL-6) production by mouse fibroblasts. Methods: Sixty seconds of pre-irradiation time with curcumin 500 mg/L and Led wavelength (lambda) 480 nm, 72 J cm(2), for 300 s was used for PDT. Solutions were diluted in culture medium DMEM (1 x 10(4) cells) and placed into 24-well cell culture plates with mouse fibroblasts L-929. Culture medium was used as control. After 6,24 and 48 h, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay (MIT) was used to evaluate the cell viability and the supernatant was collected for cytokine evaluation using enzyme-linked immunosorbent assay (ELISA). The results were statistically analyzed by ANOVA and BonFerroni correction (p < 0.05) for MIT and Kruskal-Wallis test and Dunn (p < 0.05) for ELISA. Results: PDT and saline solution presented low cytotoxic effect similar to the control group (p > 0.05) while 5% NaOCl was more cytotoxic than PDT (p < 0.05) in all periods of time. All materials similarly expressed IL-1 beta and IL-6 regardless to the experimental period (p < 0.05). Conclusions: PDT with curcumin was not cytotoxic to L929 fibroblasts differently from 5% NaOCl. In all groups occurred similar expression of IL-1 beta and IL-6. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Endodontic treatment; Root canal irrigants; Photodynamic therapy; Cytotoxicity; Cytokine